Successful withdrawal of catecholamine with ivabradine administration in catecholamine-dependent heart failure. Issue 6 (June 2022) - Azuma, Kohei; Asakura, Masanori; Nishimura, Koichi; Tahara, Saki; Matsumoto, Yuki; Manabe, Eri; Min, Kyung-Duk; Ishihara, Masaharu
Abstract: Ivabradine is a heart rate (HR)-lowering agent that blocks hyperpolarization-activated cyclic nucleotide-gated channel in the sinus node without a negative inotropic effect on cardiac function. Here we report a case of catecholamine-dependent heart failure, who was intolerant to β blockers, and successfully withdrew catecholamine by administering ivabradine. A 39-year-old male acute decompensated heart failure (ADHF) patient with severe systolic cardiac failure, refractory to diuretic and dobutamine treatment was transferred to our hospital. In addition to titration of dobutamine support, intra-aortic balloon pump, mechanical ventilation, and continuous hemodiafiltration therapy were initiated. These mechanical supports could stabilize ADHF and were removed. Upon stabilization of ADHF, we attempted to initiate a low dose of bisoprolol and taper dobutamine, but the patient could not tolerate even a low dose of bisoprolol nor tapering of dobutamine. Since his HR was consistently above 100 beats per minute and ivabradine was reported to improve stroke volume (SV), we initiated ivabradine, and his SV remarkably increased after initiation. Consequently, the dose of dobutamine was successfully tapered. Also, additional clinical advantage of ivabradine, assessed through hemodynamic parameters, appeared to be a reduction in afterload. <Learning objective: Ivabradine is a heart rate (HR)-lowering agent that blocks the hyperpolarization-activated cyclic nucleotide-gated channel in the sinus node without a negative inotropic effect. In this present catecholamine-dependent advanced heart failure case, the patient could not tolerate even a low dose of bisoprolol nor tapering of dobutamine. Being intolerant to beta-blockers, we initiated the administration of ivabradine. And the initiation of ivabradine resulted in not only the reduction of HR, but also the improvement in stroke volume resulting in the reduction of afterload.>